2016
DOI: 10.1007/s10067-016-3465-9
|View full text |Cite
|
Sign up to set email alerts
|

The additional benefit of ultrasonography to 2010 ACR/EULAR classification criteria when diagnosing rheumatoid arthritis in the absence of anti-cyclic citrullinated peptide antibodies

Abstract: The aim of this study was to assess the benefit of ultrasonography (US) contributing to 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria in diagnosing rheumatoid arthritis (RA), when anti-citrullinated protein (CCP) antibody and radiographic erosions are absent. Ninety-four patients suffering from arthritis of at least one joint in hands, symptom duration of less than 2 years, normal radiographs at baseline, and negative anti-CCP had 22 joint US ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
0
24
0
3
Order By: Relevance
“…The added value of US has been advocated at all levels of the disease stages4: from predicting diagnosis,1 to supporting the diagnostic and classification process,5 guiding treatment choices and response,6 predicting structural damage and flares,7 8 and influencing the concept and management of remission and treatment tapering 9 10. US has been shown to be superior to clinical assessment in detecting inflammation by assessing the presence of the most important elementary lesions in RA: synovial hypertrophy (SH), synovial effusion (SE) and Power Doppler activity (PD) 2.…”
mentioning
confidence: 99%
“…The added value of US has been advocated at all levels of the disease stages4: from predicting diagnosis,1 to supporting the diagnostic and classification process,5 guiding treatment choices and response,6 predicting structural damage and flares,7 8 and influencing the concept and management of remission and treatment tapering 9 10. US has been shown to be superior to clinical assessment in detecting inflammation by assessing the presence of the most important elementary lesions in RA: synovial hypertrophy (SH), synovial effusion (SE) and Power Doppler activity (PD) 2.…”
mentioning
confidence: 99%
“…Early RA is characterized by synovitis [6], but it may be difficult to detect subclinical synovitis during physical examination [178]. ACPA and MSUS are valuable tools to aid early diagnosis of RA [179][180][181].…”
Section: Discussionmentioning
confidence: 99%
“…In two studies the presence of clinically evident inflammatory arthritis was not required for inclusion. [12, 13] Another study showed associations between ultrasound-detected synovitis and fulfilment of the 2010-criteria, but test characteristics with and without the use of ultrasound were not provided. [15] One study calculated test characteristics and showed that the use of ultrasound resulted in an increased sensitivity at the cost of specificity, which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%